Examination of an Anecdotal “October Disappearance” of Northern Bobwhite in the Rolling Plains of Texas Through Demographic Data - Jessica A. Mehta; Rowdy A White; Joshua B. Luft; C. Brad Dabbert (National Quail Symposium Proceedings, 2022)
Landowners and wildlife managers in the Rolling Plains ecological region of Texas, USA often report encountering northern bobwhite (Colinus virginianus; hereafter, bobwhite) in summer but observe what they perceive as a decrease in quail by early to mid-fall. As most bobwhite research in the Rolling Plains is focused on either breeding season or overwinter survival and movement, researchers rarely record demographic data during this late summer and early fall period. We examined weekly survival probabilities of bobwhite (n = 244) across 7 sites in the western Rolling Plains Ecoregion from August to late November in 2016, 2017, 2019, and 2020. Bobwhites were captured and equipped with very high frequency (VHF) transmitters and tracked 1–5 times/week. We used Akaike’s Information Criterion adjusted for small sample sizes (AICc) to evaluate a suite of candidate models comparing survival among and between years and survival between individual weeks to determine whether an unreported population decrease occurred during the study years. Our comparison of weekly survival probabilities considered survival to be different if 95% confidence intervals did not overlap. Our best supported model held survival constant among years and allowed survival to vary week by week. All other models received little support (ΔAICc > 14.0). Examination of weekly survival probabilities failed to support a demographically driven hypothesis for decreased bobwhite observations from August to November. Though there was an observed decrease of weekly survival in the fourth week of September, it was not different than 16 of the 17 other weeks. We conclude that, for the years we measured, there was no support for a mass die-off hypothesis. Factors outside survival (e.g., a change in bobwhite behavior) may be driving the difference in detectability between late summer and late fall in the Rolling Plains of Texas.
Keywords: Colinus virginianus; northern bobwhite; Rolling Plains; survival; Texas.